2022
DOI: 10.3390/pharmaceutics14051071
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Asiaticoside from Centella erecta (Apiaceae) as Potential Apyrase Inhibitor by UF-UHPLC-MS and Its In Vivo Antischistosomal Activity

Abstract: Schistosomiasis, caused by parasites of the genus Schistosoma, is a neglected disease with high global prevalence, affecting more than 240 million people in several countries. Praziquantel (PZQ) is the only drug currently available for the treatment. S. mansoni NTPDases (known as SmNTPDases, ATP diphosphohydrolases or ecto-apyrases) are potential drug targets for the discovery of new antischistosomal drugs. In this study, we screen NTPDases inhibitors from Centella erecta (Apiaceae) using an ultrafiltration co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…However, under intraperitoneal administration, both free licochalcone A and L-SLNs significantly decreased worm burden and intestinal egg load [62] Carvacryl acetate Oral 100, 200, or 400 mg/kg/day Carvacryl acetate (400 mg/kg) showed moderate efficacy against S. mansoni, with slightly reduced worm burden (32-40%). Egg production was markedly reduced (70-80%) [63] Cardamonin Oral 400 mg/kg/day Oral treatment with cardamonin (400 mg/kg) demonstrated efficacy against S. mansoni, with decreased total worm load in 46.8% of mice and a 54.5% reduction in egg numbers [64] Asiaticoside Oral 400 mg/kg/day A single oral dose (400 mg/kg) of asiaticoside presented significant in vivo antischistosomal efficacy, markedly decreasing total worm and egg burden [65] Plumbagin Intraperitoneal 20 mg/kg/day Mice treated with plumbagin (20 mg/kg) showed reductions of 64.28% and 59.88% in male and female worms, respectively. Plumbagin treatment also alleviated schistosome-induced hepatosplenomegaly and reduced hepatic granuloma and liver collagen content [66] Juglone Intraperitoneal 2 mg/Kg/day Treatment with the compound reduced male and female worms by 63.1% and 52.1%, respectively.…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, under intraperitoneal administration, both free licochalcone A and L-SLNs significantly decreased worm burden and intestinal egg load [62] Carvacryl acetate Oral 100, 200, or 400 mg/kg/day Carvacryl acetate (400 mg/kg) showed moderate efficacy against S. mansoni, with slightly reduced worm burden (32-40%). Egg production was markedly reduced (70-80%) [63] Cardamonin Oral 400 mg/kg/day Oral treatment with cardamonin (400 mg/kg) demonstrated efficacy against S. mansoni, with decreased total worm load in 46.8% of mice and a 54.5% reduction in egg numbers [64] Asiaticoside Oral 400 mg/kg/day A single oral dose (400 mg/kg) of asiaticoside presented significant in vivo antischistosomal efficacy, markedly decreasing total worm and egg burden [65] Plumbagin Intraperitoneal 20 mg/kg/day Mice treated with plumbagin (20 mg/kg) showed reductions of 64.28% and 59.88% in male and female worms, respectively. Plumbagin treatment also alleviated schistosome-induced hepatosplenomegaly and reduced hepatic granuloma and liver collagen content [66] Juglone Intraperitoneal 2 mg/Kg/day Treatment with the compound reduced male and female worms by 63.1% and 52.1%, respectively.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…The oral administration of different natural compounds at doses ranging between 1.5 and 400 mg/kg demonstrated variable worm and egg burden reduction (31.8 to 100%) in infected mice [44,53,54,60,63,64]. In addition, Carvalho et al [65] demonstrated the effective antischistosomal activity of asiaticoside (400 mg/kg) against Schistosoma spp. by inhibiting SmNTPDases-enzymes found in the worm tegument-which resulted in significantly reduced worm burden.…”
Section: Initial Work Bymentioning
confidence: 99%